THE LEGAL PRINCIPLE OF THE NEWEST SYSTEM OF UKRAINIAN LAW IN THE ACTIVITY OF THE JUDICIARY IS LEGALIZED - Кельман, Михайло Степанович; Риженко, Ігор Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Objective: to study the rule of law as a principle in the judiciary in such aspects as to clarify the origins of the idea of the rule of law, the relationship between the concepts of the rule of law and the judiciary, analysis of relevant doctrine in Ukraine. Methods: dialectical, hermeneutic, prognostic, comparative-legal, formal-logical, method of modeling, decomposition, complex analysis, intersectoral method of legal research, logical methods that were used as tools to achieve this goal. Results: applying the principle of the rule of law, the judge must remember it as a global goal of justice - the rule of law in society. The resolution of every dispute and any legal conflict must be aimed at adhering to this principle. Discussion: from a practical point of view, the rule of law determines the place of the judiciary in the system of public power, which should attest not only to the real separation of powers but also to the judiciary’s ability to limit the discretion of the legislature and the executive. This is possible only if the court (and justice procedures) are independent of other branches of government. This approach to the relationship between the separation of powers (traditionally - an element of the concept of the rule of law) brings together the concept of the rule of law and the idea of the rule of law in modern conditions. The principle of the rule of law in the modern state is studied. Emphasis is placed on the scope of the rule of law, which includes: legality, which provides for a transparent, accountable and democratic process for the implementation of legal provisions; legal certainty; prohibition of arbitrariness; access to justice; respect for human rights; prohibition of discrimination; equality before the law. Conceptually, the rule of law is to limit the arbitrariness of public authority over society and the individual. Different ways of establishing the system of the rule of law (the court through the application of human rights directly forms the system of the constitution - the English tradition; it is created by the people through the exercise of constituent power - the European continental tradition) are not fundamental. From a practical point of view, the rule of law determines the place of the courts in the system of public power, which must attest not only to the real separation of powers but also to the judiciary’s ability to limit the discretion of the legislature and executive. This is possible only if the court (and justice procedures) are independent of other branches of government. This approach to the relationship between the separation of powers (traditionally an element of the rule of law) brings together the concepts of the rule of law and the rule of law. The article is devoted to a comprehensive study of the theoretical foundations of judicial law enforcement in Ukraine as a special process of practical achievement of the rule of law in the daily activities of courts, carried out after the constitutional reform of justice in 2016-2017. The acute theoretical and applied need to find ways and means to ensure the unity of law enforcement after this reform, which allowed to form a new scientific approach to solving problems of judicial law enforcement. The problem is solved with the help of intersectoral methodology and integration in law, given the expansion of the functions of the judiciary, in particular, in terms of increasing the law-making role of courts (the theory of «soft» separation of state power). The article proves that the current state of transit legislation in Ukraine leads to the fact that the courts of first instance (sometimes - the appellate court as courts of first instance) take on challenges - to consider the case, guided by the rule of law, taking into account not only the balance of public and private interests, but often the existence of gaps in laws or applying poor quality legislation. The result of judicial enforcement in such cases is the completion of a rule of law, which in fact can be considered a judicial rule and become the basis for the emergence of a new law, the maintenance of which during the review of the court decision gives it a precedent, and thus lower courts promote judicial supremacy.